Caracterización anatómica cuantitativa, cualitativa y cambios intraanuales en la madera de 10 árboles urbanos de la ciudad de Loja - Cueva Briceño, Eva Fernanda (2023)
Loja's urban tree species provide multiple ecosystem services. However, the scarcity of knowledge on the growth dynamics of trees in urban ecosystems hinders their management and correct use in tree planting plans. Due to this, the present study aims to analyze qualitatively, quantitatively, and intra-annually the anatomical features of the wood of the 10 most frequent forest species in Loja. The database of the 17-DI-FARNR-2021 project of urban trees of the National University of Loja was used for the selection of the species. Three study sectors were established in the city (north, center, and south) with three replicates per species in each sector. Small wood cores of 5 cm in length and 0.5 cm in diameter were taken with a Pressler borer, and eventually, they were analyzed and evaluated in the Tropical Wood Anatomy laboratory of the National University of Loja, 87 anatomical features in the broadleaf trees, and 42 characteristics in conifers based on IAWA standards. Data visualization was done through boxplots, correlation matrices (significant r with p < 0.05), and vertex plots evaluated with the Kruskal-Wallis test method through the statistical software environment R. Nevertheless, the growth site of urban trees in Loja does influence the quantitative anatomical features of the wood, but not the qualitative ones. As a rule, the nine broadleaf forest species were characterized by solitary vessels, alternate pits, thin to thick fiber walls, and procumbent cell rays in the 1- and 3-series. Grevillea robusta and Fraxinus chinensis were the species with the highest number of vessels. Cedrela montana, Alnus acuminata, Fraxinus chinensis, Jacaranda mimosifolia and Salix humboldtiana were the only species showing visible growth rings. At the intra-annual level, vessel and fiber diameter were the main characteristics to differentiate earlywood from latewood. In conclusion, anatomical features, especially quantitative ones such as vessel diameters and length, are excellent indicators of species' adaptation to different sectors in the city of Loja. Key words: wood anatomy, intra-annual changes, quantitative changes, qualitative changes, urban trees, Loja.